The stoic origins of Erasmus' philosophy of Christ - Dealy, Ross (Toronto ; Buffalo ; London : University of Toronto Press, 2017)
"This study focuses on Erasmus' two-dimensional grasp of Stoicism evident in his edition of De officiis (1501) and the huge implications he saw for religion. The author argues that "The Philosophy of Christ' for which Erasmus is famous is a Christian version of Stoicism."--
Part VI: Beyond Devotionalist AssumptionsPart VII: Spiritual Warfare: Christianizing Katorthoma/Kathekon: The Enchiridion militis christiani; 1 Correcting Origen on Indifferentia; 2 Correcting Origen and Socrates on the Origins of Human Diversity; 3 Not Flesh/Spirit but Indifferens/Spirit; 4 A New Type of Warfare: Syncretizing Two Opposite Types of Value; Conclusion; Bibliography; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 2, 2017).
In English.
JSTOR
Keywords: Erasmus, Desiderius, -- -1536 -- Criticism and interpretation; Jesus Christ; Érasme, -- -1536 -- Critique et interprétation.; Jésus-Christ.; Erasmus, Desiderius, -- -1536; Jesus Christ; Stoics; Stoïcisme.; stoicism; PHILOSOPHY -- History & Surveys -- Modern; PHILOSOPHY -- History & Surveys -- Renaissance; Stoics; Criticism, interpretation, etc